2017
DOI: 10.20429/ijsotl.2017.110111
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Student Outcomes in Play Therapy: A Qualitative Case Study Design

Abstract: Outcome research examining the effectiveness of teaching methods in counselor education is sparse. The researchers conducted a qualitative investigation utilizing an instrumental case study to examine the influence of a constructivist-developmental format on a play therapy counseling course in a large CACREP accredited university in the Southeastern United States. Results indicated that the constructivist-developmental lens was effective in promoting the professional development of counselors-in-training. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…According to Maria [26] there are stages of simulation design that are required for students' decision making and they include identifying a problem, formulation of a problem, collect and process real system data, formulate and develop a model, validate the model, document model for future use. As a result.…”
Section: Simulation Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Maria [26] there are stages of simulation design that are required for students' decision making and they include identifying a problem, formulation of a problem, collect and process real system data, formulate and develop a model, validate the model, document model for future use. As a result.…”
Section: Simulation Modelmentioning
confidence: 99%
“…According to Maria [26], simulations are significant in a number of ways, however, if the aim is to equip students with psychomotor skills, teachers must display understanding of simulation skills. This includes helping students to identify a problem, formulate the problem, collecting, and processing real system data, formulating and developing a model, validating the model and documenting the model.…”
Section: The Importance Of Simulations Skills In the Design Processmentioning
confidence: 99%
See 2 more Smart Citations
“…No studies have been published on a combination of licensed counselors and elementary school counselors as participants. The review also demonstrated that most of the research about play therapy training consisted of program evaluations for graduate-level play therapy courses (Dillman Taylor et al, 2017; Lindo et al, 2012); as evaluations of continuing education units (Lambert et al, 2007; Ray et al, 2005); or as evaluations of short-term, self-produced workshops on play therapy for school counselors (Kagan & Landreth, 2009; Pereira & Smith-Adcock, 2013; Shin & Gonzalez, 2018). Therefore, an assessment of the variety of training sources and professional development for counselors in play therapy was needed, particularly for working counselors who are licensed.…”
mentioning
confidence: 99%